Abolished ventilation and perfusion of lung caused by blood clot in the left main bronchus: auto-downregulation of pulmonary arterial blood supply. (15th September 2015) - Afzelius, P; Bergmann, A; Henriksen, JH
Abstract : It is generally assumed that the lungs possess arterial autoregulation associated with bronchial obstruction. A patient with pneumonia and congestive heart failure unexpectedly developed frequent haemoptysis. High-resolution CT and diagnostic CT were performed as well as ventilation/perfusion (V/Q) scintigraphy with single-photon emission CT (SPECT)/CT. V/Q SPECT/CT demonstrated abolished ventilation due to obstruction of the left main bronchus and markedly reduced perfusion of the entire left lung, a condition that was completely reversed after removal of a blood clot. We present the first pictorially documented case of hypoxia-induced pulmonary vasoconstriction and flow shift in a main pulmonary artery due to a complete intrinsic obstruction of the ipsilateral main bronchus. The condition is reversible, contingent on being relieved within a few days.